2021
DOI: 10.1186/s12859-020-03936-1
|View full text |Cite
|
Sign up to set email alerts
|

MADGAN: unsupervised medical anomaly detection GAN using multiple adjacent brain MRI slice reconstruction

Abstract: Background Unsupervised learning can discover various unseen abnormalities, relying on large-scale unannotated medical images of healthy subjects. Towards this, unsupervised methods reconstruct a 2D/3D single medical image to detect outliers either in the learned feature space or from high reconstruction loss. However, without considering continuity between multiple adjacent slices, they cannot directly discriminate diseases composed of the accumulation of subtle anatomical anomalies, such as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 61 publications
0
94
0
Order By: Relevance
“…Recently, some works studied GAN applications with and without MAR [ 40 , 41 ]. These studies applied GAN technology to the reconstructed image to improve the accuracy of the tomographic image in the in-plane and longitudinal directions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some works studied GAN applications with and without MAR [ 40 , 41 ]. These studies applied GAN technology to the reconstructed image to improve the accuracy of the tomographic image in the in-plane and longitudinal directions.…”
Section: Discussionmentioning
confidence: 99%
“…Han [40] proposed an unsupervised medical anomaly network model to detect unsupervised medical anomalies (MADGAN). A new two-step method that uses GANbased multiple contiguous MRI slice reconstruction to detect brain abnormalities at different stages on multi-structured MRI: (reconstruction) Wasserstein loss with graded penalty + 100, 1 loss − 1.…”
Section: Related Workmentioning
confidence: 99%
“…It is a conditional GAN which uses MRIs such as FLAIR and T1 contrast images in place of noise vectors. Another example is the Medical Anomaly Detection GAN (MADGAN) [21], which also takes advantage of the aforementioned attention mechanism. Although this model is used for classification, a recent study has shown its very pertinent applications in both MRI reconstruction and lesion detection [21].…”
Section: Generative Adversarial Networkmentioning
confidence: 99%